How does Chile develop strategies of wine-growing and wine-making communication? - Rouvellac, Eric (Geographicalia, 2017)
The vine growing in Chile is a history rising in conquistadors’ times, but the modernization of this one and its access to the massive exportis recent, going back to 1980’s. Without internal market worthy of the name, the country builds little by little an effective communication to sell its wines abroad. It is so on one hand that the isolation is used as communications tool with the sanitary pretext of absence of outside influences. For example the conservation of the phylloxera is moved forward as a strong communication tool, or the originality was maintained around the vine Carménère. On the other hand is developed a communication around the vineyard and around the wine, being inspired by the architecture iconoclastic as a vineyard and wine entrance or of the strength of the winemaking tours. The communication is also turned towards the environment, with the objective to respect a winemaking charter in sustainable development. Is it the real will or only greenwashing? The results in half complexion show especially that the environment is a tool in the service of the communication.
Keywords: Wine-making communication; isolation; grafting; vine Carménére; architecture of winery; wine-making tour; sustainable development; Chile.